Arab Studies in Lithuania During 19–20 C. - Mikalauskas, Valdas (Acta Orientalia Vilnensia, 2000)
The article examines the history of Arab world explorations on the part of Lithuania’s scientists and amateurs such as travellers.Arab studies in Lithuania are closely connected with Vilnius University at the first three decades of 19 c. Academic atmosphere created by two great humanitarians J. Lelevel and G. Grodek encouraged formation of group of student enthusiasts interested in Orient. This enthusiasm needed to be transformed into academic studies. University lacked professional orientalists. Those who were foreigners didn’t meet students’ needs. It was decided to foster professor of oriental languages from local students. One of them J. Senkowski was very promising: being 18 years old he from Arabic language translated and published “Lokman’s fables”. This translation is considered to be the first one in polish literature’s history. After being dispatched to eastern countries to gain the needed knowledge. J. Senkowski didn’t return to Vilnius for academic purposes. Some of the students interested in eastern countries proved later to become orientalists of the world fame. J. Kowalewski is world famous scientist of Mongol studies, A. Zaba one of the first explored Turkish and Iraqi Kurds. A. Muchlinski became professor of oriental languages at Sankt–Petersburg University. Others like I. Pietraszewski, J. Wiernikowski, A. Chodžka also contributed to the orientalism and in one way or other to Arab studies.All above–mentioned people were forced to continue their academic activity outside Lithuania after the closure of Vilnius University in 1832.At the second half of 19 c. there are no professional orientalists in Lithuania. V Girgas Russian scientist of Lithuanian origin worked at Sankt–Petersburg University specialising in Arabic literature.Some useful information about Arabic countries, especially Egypt, give us two famous travellers of 19 c. M. Tiškevičius and I. Žagelis.After the IWW when Lithuania gained independence from Russia not much could be said about Arab studies. That was caused by small country’s minimised interests in Arab region.There are a lot of translations of Arab literature during soviet occupation period, but all of them are made not from original language.The situation is changing after 1990. Arabic language and subjects on Arab culture are taught at Vilnius University Centre of Oriental Studies.